Methods of improving the lightning performance of 22 kV circuit underbuilt on 115 kV transmission lines - Thanaphong Thanasaksiri (2018)
This paper presents the analysis of lightning overvoltages of 22 kV. overhead distribution line underbuilt on 115 kV. transmission line circuit to investigate the options for increasing the lightning performance. Improvement efforts could include better grounding, higher critical flashover voltage (CFO) and arresters installation. The analysis of lightning overvoltages are performed using ATPDraw version of ElectroMagnetic Transients Program (EMTP). Models of system studied have also been presented.